Laboratory Diagnosis of Mumps in a Partially Immunized Population: The Nova Scotia Experience - TF Hatchette; R Davidson; S Clay; J Pettipas; J LeBlanc; S Sarwal; M Smieja; KR Forward (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: In 2007, Atlantic Canada experienced a large outbreak of mumps predominately in university students who had received a single dose of measles, mumps and rubella vaccine. The present study describes the performance characteristics of reverse transcriptase polymerase chain reaction (RT-PCR) on buccal and urine specimens and immunoglobulin M (IgM) serology in this partially immune population.